BARTON, D. & HAMILTON, M. LOCAL LITERACIES: READING AND WRITING IN ONE COMMUNITY. LONDRES E NOVA YORK: ROUTLEDGE, 1998, 299 PÁGS. - Santos, Edna Cristina S. (Cadernos de Linguagem e Sociedade, 2010)
BARTON, D. & HAMILTON, M. LOCAL LITERACIES: READING AND WRITING IN ONE COMMUNITY. LONDRES E NOVA YORK: ROUTLEDGE, 1998, 299 PÁGS.